Romantic poetry - Esterhammer, Angela (Comparative history of literatures in European languages ;, 2002)
Romantic Poetry encompasses twenty-seven new essays by prominent scholars on the influences and interrelations among Romantic movements throughout Europe and the Americas. It provides an expansive overview of eighteenth- and nineteenth-century poetry in the European languages. The essays take account of interrelated currents in American, Argentinian, Brazilian, Bulgarian, Canadian, Caribbean, Chilean, Colombian, Croatian, Czech, Danish, English, Estonian, Finnish, French, German, Greek, Hungarian, Irish, Italian, Mexican, Norwegian, Peruvian, Polish, Romanian, Russian, Serbian, Slovak, Spanish.